2013
DOI: 10.1007/s00217-013-2041-7
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities and bioactive components in some berries

Abstract: The objective of this study was to evaluate the antioxidant and binding effects of gooseberry, a less-studied berry, and to compare with blueberry and cranberry in the model of interaction with human serum albumin (HSA). The relationship between the scavenging properties of dietary polyphenols of the selected berries and their affinities for HSA were investigated by fluorescence analysis. In order to perform the extraction and identification of the antioxidants present in the samples, different types of extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 38 publications
4
19
3
Order By: Relevance
“…According to Oszmiański et al [28], the antioxidant capacity measured by the ABTS and FRAP assay in cranberry cultivars 'Pilgrim', 'Stevens', and 'Ben Lear' was around 2 times higher and around 3 times lower than antioxidant capacity in the same cultivars of cranberry harvested at different maturity stages. Namiesnik et al [39] reported that antioxidant capacity measured by ABTS assay ranged from 10.72 to 72.76 μmol/g dm, while FRAP assay values ranged from 3.28 to 26.97 μmol/g dm, which was lower than our results. The antioxidant capacity (as with the ABTS and FRAP assay) increased remarkably in fruit cvs.…”
Section: Antioxidant Capacitycontrasting
confidence: 98%
“…According to Oszmiański et al [28], the antioxidant capacity measured by the ABTS and FRAP assay in cranberry cultivars 'Pilgrim', 'Stevens', and 'Ben Lear' was around 2 times higher and around 3 times lower than antioxidant capacity in the same cultivars of cranberry harvested at different maturity stages. Namiesnik et al [39] reported that antioxidant capacity measured by ABTS assay ranged from 10.72 to 72.76 μmol/g dm, while FRAP assay values ranged from 3.28 to 26.97 μmol/g dm, which was lower than our results. The antioxidant capacity (as with the ABTS and FRAP assay) increased remarkably in fruit cvs.…”
Section: Antioxidant Capacitycontrasting
confidence: 98%
“…The AOP of dried cranberries with added vit. C is almost two orders of magnitude higher than that of dried cranberry fruits, which in comparison to literature AOP data is of similar range though somewhat lower, 17,27 most probably due to losses incurred during drying and storage, since the published data were obtained by analysing fresh fruit. The labelled content of ascorbic acid (AA) in the enriched cranberry food supplement amounts to 1.4 mmol/g.…”
Section: Aop Of Selected Drinks and Food Supplements Obtained By Dsupporting
confidence: 62%
“…[15][16][17][18][19][20] The primary purpose of the present study was to demonstrate how the selected method and composition of the assay solvent influence the reactivity of antioxidant compounds in the above mentioned foods with chromogenic radicals, DPPH…”
Section: Introductionmentioning
confidence: 99%
“…The fruits are eaten raw or processed (via juices, jellies, dehydrated) (Puente et al, 2011). The berries stand out because of their exotic taste and high mineral content, antioxidants, and medicinal and bioactive substances (Puente et al, 2011;Ramadan, 2012;Rop et al, 2012;Rutz et al, 2012;Namiesnik et al, 2013;Bravo et al, 2014;Fischer et al, 2014;Moneim et al, 2014;Al-Olayan et al, 2014;Ahmed, 2014).…”
Section: A B Cmentioning
confidence: 99%